Порушення вуглеводного обміну, виявлені у скринінгу дорослого населення двох районів м. Харкова - Кравчун, Н. О.; Романова, І. П.; Козаков, О. В.; Сороколат, Ю. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
The article presents data of the screening based on determining the levels of fasting glucose, glycosylated hemoglobin, C-peptide, immunoreactive insulin and the results of oral glucose tolerance test in order to improve the detection of type 2 diabetes.